Severe Acute Hypertension and End-Organ Damage. Do We React Fast Enough? - Caldentey, Guillem; Giralt, Teresa; Llagostera, Marc; Ribas, Núria; Recasens, Lluis; Xavier, Quiroga; Vaquerizo, Beatriz (Cardiology and Cardiovascular Medicine, 2019)
Abstract not available in the source database.